A community-based approach to analyzing the ecotoxicity of nitrofurazone using periphytic protozoa. (February 2022) - Kazmi, Syed Shabi Ul Hassan; Uroosa,; Xu, Henglong; Warren, Alan
Abstract: The ecotoxicity of nitrofurazone was analyzed based on a community-based approach using periphytic protozoa. Median lethal concentrations ( LC 50 ) within an exposure time of 30 min were determined by an acute toxicity test at 0, 1.5, 3, 6 and 12 mg ml −1 nitrofurazone. Toxicity curve tests demonstrated a decreasing trend with increasing exposure time and was well fitted to the toxicity equation LC 50 = 32.85e -0.8143 t ( t = exposure time; R 2 = 0.91; P < 0.05). Median inhibition concentrations ( IC 50 ) for periphytic protozoan growth rates were obtained by chronic tests at 0, 1, 2, 4 and 8 mg ml −1 nitrofurazone within 10 days exposure and were well fitted to the equation r % = 0.3686e -0.35 Cnit ( C nit is the concentration of nitrofurazone; R 2 = 0.92 and P < 0.05). These findings suggest that the LC 50 and IC 50 values of nitrofurazone can be predicted for any exposure time using periphytic protozoan communities as a bioassay model. Highlights: Nitrofurazone showed toxicity effects on protozoan periphytons at community level. Median lethal concentration LC 50 values well fitted to a toxicity curve equation. Median inhibitory concentration IC 50 values decreased with exposure time. The LC 50 and IC 50 values of nitrofurazone can be predicted for any exposure time. Protozoan periphytons may be used as a bioassay community.